2017
DOI: 10.1007/s11130-017-0630-5
|View full text |Cite
|
Sign up to set email alerts
|

Ripe Banana Flour as a Source of Antioxidants in Layer and Sponge Cakes

Abstract: About one-fifth of all bananas harvested become culls that are normally disposed of improperly. However, ripe banana pulp contains significant amounts of fibre and polyphenol compounds as well as a high content of simple sugars (61.06g/100g), making it suitable for sucrose replacement in bakery products. This work studied the feasibility of incorporating ripe banana flour (20 and 40% of replacement) in cake formulation. Physical, nutritional and sensory attributes of sponge and layer cakes were evaluated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 28 publications
2
23
0
9
Order By: Relevance
“…Green tea powder substituting some flour in sponge cakes pro duced a green tea cake with more effective antioxidant properties, as well as higher content of dietary fibre [6]. In other studies [7] banana powder was replaced with flour. According to the results, sponge and layer cakes with the inclusion of ripe banana generally led to a decline in the specific volume and hardness compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…Green tea powder substituting some flour in sponge cakes pro duced a green tea cake with more effective antioxidant properties, as well as higher content of dietary fibre [6]. In other studies [7] banana powder was replaced with flour. According to the results, sponge and layer cakes with the inclusion of ripe banana generally led to a decline in the specific volume and hardness compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…Ripe banana pulp is rich in fibre, polyphenols and simple sugars (61.1 g/100 g) making it ideal for sucrose replacement in baked products. However, in cake formulation inclusion of ripe banana flour slightly lowered the specific volume and increased hardness [22]. Consequently, a decline in sensory acceptability.…”
Section: Sensory Acceptability Of Banana Peel and Flour In Food Productsmentioning
confidence: 98%
“…Ripe banana pulp is high in fibre, polyphenol compounds and simple sugars (61.1 g/100 g). Segundo et al [22] reported the potential of ripe banana flour [RBF] (20 and 40% replacement) as sucrose replacer in cake formulation. The inclusion of RBF significantly increased the dietary fibre, polyphenols and antioxidant capacity to three-fold.…”
Section: Sensory Acceptability Of Banana Peel and Flour In Food Productsmentioning
confidence: 99%
“…Beside the aforementioned (Section 3) health benefits of banana due to its contents of antioxidant components (often referred to bioactive compounds), vitamins and nutrient precursors, as well as dietary fiber; it should be noted that resistant starch [81], one of the most important dietary fibers mainly obtained from green banana via drying, has increasingly gained attention for its capability of bringing about the production of 4C or 4C-less fatty acids for prevention of carcinogens in the human colorectal track [83,84]. Therefore, value-added sustainable drying processes can allow resistant starch RS derived from green banana to be one of the healthy food ingredients [85], promote the phenolic acid contents in green banana pulp flour (GBPuF) with improved physicochemical properties [85][86][87][88], and retain the color attributes of yellow/green banana peel flour (YBPeF/GBPeF) [89][90][91]. The unbalanced supply-demand cycle due to overproduction can also be reliably relieved.…”
Section: Dried Pulp/peel Flour Of Banana (Fruit)mentioning
confidence: 99%
“…Regardless of the operation cost, freeze drying is versatile for maintenance of color against browning reaction for most of the banana coproduct parts, i.e., GBPeF, GBPuF, YBPuF, and YBPeF, with the greatest total of flavonoids reported in YBPeF [89]. Accordingly, banana flours from different sustainable parts collected at various ripening stages could potentially be utilized as wheat flour or other likewise flours, with less favorable, however, acceptable viscoelastic behavior for certain consumers with health awareness; studied products include gluten-free cakes, sponge cakes, bread, snacks, ice cream, and pasta [86,87,89,91,[96][97][98]. As for considerations of color appealing attributes, drying processes facilitating moisture and oxygen depleting features would be preferred and can be studied in the future.…”
Section: Dried Pulp/peel Flour Of Banana (Fruit)mentioning
confidence: 99%